Systematic bibliometric and visualized analysis of research hotspots and trends in attention-deficit hyperactivity disorder neuroimaging - Deng, Haiyin; Huang, Zhenming; Li, Zhaoying; Cao, Lei; He, Youze; Sun, Ning; Zeng, Yi; Wu, Jingsong (Frontiers in Neuroscience, 2023)
This study aimed to explore the research hotspots, trends and frontiers of the neuroimaging of attention deficit hyperactivity disorder（ADHD）in the past 30 years. Scientific publications related to the neuroimaging of ADHD from 1992 to 2022 were retrieved from the Web of Science database. The retrieved information was analyzed using CiteSpace 6.1.R3 and Scimago Graphica 1.0.25. Bibliometric visualization analysis of countries/regions, institutions, authors, journals, keywords and references were conducted. A total of 2621 publications were retrieved. The number of annual related publications remarkably increased over the years. These publications mainly come from 65 countries/regions led by the United States and 435 institutions. Kings’ college London had the highest number of publications. We identified 634 authors, among which Buitelaar, J.K. published the largest number of articles and Castellanos FX was co-cited most often. Not only did the journal of Biological psychiatry have the most papers, but it was also cited the most. In recent years, burst keywords were resting-state fMRI, machine learning, functional connectivity, and networks. And a timeline chart of the cluster of keywords showed that "children" had the longest time span. And burst references included and a series of references with citation bursts have provided clues to the frontiers of research. Increased attention has been paid to ADHD neuroimaging. It is hoped that this work may help researchers to identify new perspectives on potential collaborators and cooperative institutions, hot topics and research frontiers.